Garnet-type Mn(3)Cr(2)(GeO(4))(3) - Lipp, Christian (International Union of Crystallography, 2012)

(untitled)
Single crystals of garnet-type trimanganese(II) dichromium(III) tris[orthogermanate(IV)], Mn(II) (3)Cr(III) (2)(GeO(4))(3), were obtained by utilizing a chemical transport reaction. Corresponding to the mineral garnet with the general formula A (II) (3) B (III) (2)(SiO(4))(3), each of the four elements occupies only one crystallographically distinct position. Mn(2+) occupies the respective A position (Wyckoff site 24c, site symmetry 2.22), being surrounded by eight O atoms that form a distorted cube [d(Mn—O) = 2.291 (2) and 2.422 (2) Å, 4× each], while Cr(3+) on the B position (Wyckoff site 16a, site symmetry .-3.) is situated in a slightly distorted octahedron of six O(2−) anions [d(Cr—O) = 1.972 (2) Å, 6×]. In addition, the O atoms on general site 96h form isolated [GeO(4)](4−) tetrahedra with Ge(4+) on site 24d [site symmetry -4..; d(Ge—O) = 1.744 (2) Å, 4×].